House dust mite allergy in Malaysia: review of research gaps in the current scenario and the way forward - Yu, Zhao Lee; Siew, Audrey Foong Kow; Jacquet, Alain; Ming, Tatt Lee; Chau, Ling Tham (Springer, 2023)
The prevalence of house dust mite (HDM) allergy, especially in Asian countries with rapid urbanization, has been increasing. House dust mites thrive in places with relatively high humidity. With the combination of climate change, naturally high humidity, and urbanization, tropical countries like Malaysia are becoming a hotspot for HDM allergy fast. With a previously reported sensitization rate of between 60 and 80%, it is a worrying trend for Malaysia. However, due to incomplete and out-of-date data, as seen by the limited study coverage in the past, these numbers do not paint a complete picture of the true HDM allergy scene in Malaysia. This review briefly discusses the HDM fauna, the HDM sensitization rate, the common diagnosis and therapeutic tools for HDM allergy in Malaysia, and makes suggestions for possible improvements in the future. This review also highlights the need of more comprehensive population-based prevalence studies to be done in Malaysia, encompassing the three main HDMs—Dermatophagoides pteronyssinus, Dermatophagoides farinae, and Blomia tropicalis—as the lack of up-to-date studies failed to give a clearer picture on the current scenario of HDM allergy in Malaysia. Future studies will be beneficial to the nation in preparing a better blueprint for the management and treatment of HDM allergy.